3 Let it all out: a scoping review of emotional disclosure-based psychological interventions in palliative care. (13th October 2019) - McInnerney, Daisy; Kupeli, Nuriye; Stone, Patrick; Anantapong, Kanthee; Chan, Justin; Candy, Bridget
Abstract : Introduction: Emotional disclosure (ED) is a term used to describe the therapeutic expression of emotion. There is some evidence to suggest physical and psychological benefits of EDbased interventions in palliative care settings. However, heterogeneity in intervention format, terminology and outcome measures has made it difficult to understand and thereby, explore how to develop a simple ED-based intervention more tailored for palliative care. Aims: To scope existing literature to develop a taxonomy of ED-based interventions for people with palliative-stage disease and their family carers. Methods: The review is guided by Arksey and O'Malley's (2005) five-stage scoping review framework. Six databases (including CINAHL and MEDLINE), grey literature, trial registers and conference proceedings were searched for relevant studies up to March 2019. Titles and abstracts were screened by 2 independent reviewers. Following full text review, data will be extracted. A taxonomy will be developed to categorise ED-based interventions. Categories will be mapped to mechanisms, intervention objectives, outcome measures and efficacy. Results: The search identified 6, 611 unique citations. Further references may be identified by hand-searching references of included articles and contacting authors. Title and abstract screening has identified 278 potentially relevant papers so far. Conclusions: Full text review of relevant citations is underway. The review will be completed by autumn 2019. The results will document how ED has been evaluated in this setting and pinpoint what elements may prove most effective and in what context. This will inform future research in the development and assessment of ED-based psychotherapeutic interventions in the palliative care setting.